Formyl Peptide Receptor 2-Dependent cPLA2 and 5-LOX Activation Requires a Functional NADPH Oxidase - Tiziana Pecchillo Cimmino; Iolanda Panico; Simona Scarano; Mariano Stornaiuolo; Gabriella Esposito; Rosario Ammendola; Fabio Cattaneo (Antioxidants, 2024)
Phospholipases (PL) A2 catalyzes the hydrolysis of membrane phospholipids and mostly generates arachidonic acid (AA). The enzyme 5-lipoxygenase (5-LOX) can metabolize AA to obtain inflammatory leukotrienes, whose biosynthesis highly depends on cPLA2 and 5-LOX activities. Formyl Peptide Receptor 2 (FPR2) belongs to a subfamily of class A GPCRs and is considered the most versatile FPRs isoform. Signaling triggered by FPR2 includes the activation of several downstream kinases and NADPH oxidase (NOX)-dependent ROS generation. In a metabolomic analysis we observed a significant increase in AA concentration in FPR2-stimulated lung cancer cell line CaLu-6. We analyzed cPLA2 phosphorylation and observed a time-dependent increase in cPLA2 Ser505 phosphorylation in FPR2-stimulated cells, which was prevented by the MEK inhibitor (PD098059) and the p38MAPK inhibitor (SB203580) and by blocking NOX function. Similarly, we demonstrated that phosphorylation of 5-LOX at Ser271 and Ser663 residues requires FPR2-dependent p38MAPK and ERKs activation. Moreover, we showed that 5-LOX Ser271 phosphorylation depends on a functional NOX expression. Our overall data demonstrate for the first time that FPR2-induced ERK- and p38MAPK-dependent phosphorylation/activation of cPLA2 and 5-LOX requires a functional NADPH oxidase. These findings represent an important step towards future novel therapeutic possibilities aimed at resolving the inflammatory processes underlying many human diseases.